Mapping research approaches to data practices in schools - Krein, Ulrike; Hartenstein, Anna; Schiefner-Rohs, Mandy (Frontiers in Education, 2022)
Digital data have a major impact on school practices and play a central role for teachers, including their pedagogical practice. From a research perspective, the question arises how data practices and data-related transformation processes in schools can be studied. Therefore, the aim of this paper is to methodically review research approaches and underlying methodological assumptions about data practices in schools based on a systematic review. The focus is on social science research designs, social science research instruments, and knowledge production methods. The article provides an overview of previous research practice in this area and concludes with possible implications for future research.